General Roots, General Spirituality: Literary Interrelations of Literatures in the Aspect of Cultural Dialogue - Gimadieva, Guluza Ilyasovna; Mingazova, Liailia Ihsanovna; Sayilov, Galib Amiruglu; Sayfulina, Fleurа Sagitivovna (Journal of History Culture and Art Research, 2017)
The article deals with the works of Turkic writers, including Tatar and Turkmen, in which a close interaction is clearly manifested at the synchronic and diachronic levels. Using the example of such works as the heroic epos "Manas", "Kitaby Dede Korkut" of Oguzes, as well as the poems of "Kissa-i Yusuf" by Kul Gali, the works of Turkmen writers Berdy Kerbabaev, Makhtumkuli, Zahir Bigiyev, Shakir Muhammadov, the literary and cultural interrelations of the Turkic peoples are revealed. The Turkmen poet Makhtumkuli is among them. There is information about the distribution of his works among the Tatars in manuscripts, some works were published in pre-revolutionary Tatar publications. The article deals with the history of creation, study, analysis and publication of the poems by Makhtumkuli in Tatar and Turkmen languages. Some of Mahtumkuli's works are in the library collections of Kazan, St. Petersburg, Ufa, as well as in private collections. Thus, the article concludes that despite the national differences of the Turkic peoples, they are united by common literary roots, common goals and interests, moral, spiritual and cultural values. The fact that the literature of the Turkic peoples is characterized by an abundance of authors and works, a variety of genres and poetic forms, ideological and thematic riches and a high artistic level is confirmed once again.